Diagnosis dan Tatalaksana Trikiasis - Keziah Tirtawijaya; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Trichiasis is a condition in which the eyelashes are in the wrong position, facing back and rubbing against the cornea or conjunctiva. In trichiasis the eyelash follicles are normal, but the direction of their growth is abnormal. Some of the eyelashes or all of the eyelashes at the eyelid margin may be involved. Trichiasis can be classified into major and minor. Trichiasis is an acquired condition, not a congenital condition. Trichiasis affects the lower eyelids, but in certain cases, such as chemical burns of both eyelids and trachoma, the upper eyelids are more affected. The cause of trichiasis is often idiopathic, but chronic eyelid inflammation or an infection such as trachoma, herpes simplex or zoster, can be the cause. Trichiasis often occurs with other diseases such as trachoma, cicatricial pemphigoid, and other eyelid trauma. Trichiasis is complicated by corneal erosion and corneal ulcers. Trichiasis can cause eye irritation. Treatment of trichiasis is divided into operative and non-operative management. Treatment of trichiasis depends on the number of eyelashes involved. Treatment of trichiasis can be in the form of using contact lenses, removing eyelashes, or surgery. This paper uses the article review method using sources such as journals and books. The purpose of this writing is to know the definition, diagnosis, and management of trichiasis. The diagnosis of trichiasis can be established by anamnesis and physical examination. The management of trichiasis depends on the symptoms in the anamnesis and physical examination.